Effect of Ocean Acidification on Bacterial Metabolic Activity and Community Composition in Oligotrophic Oceans, Inferred From Short-Term Bioassays - Hu, Caiqin; Li, Xiangfu; He, Maoqiu; Jiang, Peng; Long, Aimin; Xu, Jie (Frontiers in Microbiology, 2021)
Increasing anthropogenic CO2 emissions in recent decades cause ocean acidification (OA), affecting carbon cycling in oceans by regulating eco-physiological processes of plankton. Heterotrophic bacteria play an important role in carbon cycling in oceans. However, effect of OA on bacteria in oceans, especially in oligotrophic regions, was not well understood. In our study, response of bacterial metabolic activity and community composition to OA was assessed by determining bacterial production, respiration and community composition at the low pCO2 (400 ppm) and high pCO2 (800 ppm) treatments over the short term at two oligotrophic stations in the northern South China Sea. Bacterial production decreased significantly by 17.1 - 37.1 % in response to OA, since bacteria with high nucleic acid content preferentially were repressed by OA, which was less abundant under high pCO2 treatment. Correspondingly, shifts in bacterial community composition occurred in response to OA, with a high fraction of the small-sized bacteria and high bacterial species diversity in high pCO2 scenario at K11. Bacterial respiration responded to OA differently at both stations, most likely attributed to different physiological responses of bacterial community to OA. OA mitigated bacterial growth efficiency and consequently a larger fraction of DOC entering microbial loops was transferred to CO2.